THE INFLUENCE OF WAGES, CAPITAL AND PRODUCTION VALUE ON LABOR ABSORPTION IN THE MELARAT CRAKER HOME INDUSTRY IN CIREBON - Lutfiyanti, Lutfiyanti; Fauzi, Mabruri; Agustin, Afiqoh; Jufri, Ali (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2025)
Gesik Village, Tengahtani District, Cirebon Regency, is renowned for its productivity due to the presence of numerous industries and micro, small, and medium enterprises (MSMEs), with its flagship product being 'kerupuk melarat' (a type of traditional Indonesian crackers). This 'kerupuk melarat' home industry plays a pivotal role in absorbing labor through job creation, thereby reducing the existing unemployment rate, particularly within Gesik Village itself, by recruiting workers from the local community. The aim of this research is to analyze the influence of wages, capital, and production value on labor absorption in the 'kerupuk melarat' home industry in Cirebon, specifically in Gesik Village, Tengahtani District, Cirebon Regency. This research employs a quantitative method using a saturated sampling technique. There were 32 respondents, owners of 'kerupuk melarat' home industries in Gesik Village, who were the subjects of this study. The results of this research indicate that the wage variable does not significantly influence labor absorption partially, while the capital and production value variables partially significantly influence labor absorption. Furthermore, simultaneously, the wage, capital, and production value variables significantly influence labor absorption.